The Phenomenon of Social Disintegration Through Fanwar Between K-Popers Among College Students (A Case Study at Students Who is K-Pop Fans on Twitter) - Purba, Nurwidyastuti Setiamanah; Sundawa, Dadang; Nurbayani, Siti (International Journal Pedagogy of Social Studies, 2022)
At present, social media has become a place for people around the world to interact with each other. It is also applied to K-Pop fans (K-Popers), in which they use social media to interact with their idols or their fellow fandoms (a group of fans). However, it is common when two or more people from different fandoms have an argument because of different opinions or known as fanwar. In this research, the main subject is Indonesia K-Popers students in college who do fanwars on Twitter. The purpose is to find out the reasons why college students are involved in fanwar and its effects, one of them is social disintegration. This research used a qualitative approach with case study method. The results showed that, the positive effects of fanwar are increasing their thinking skills to become more critical and increasing their debate skills. Meanwhile, for negative effects, fanwar can cause problems in friendship, especially with different fandoms, that is s why a friendship in K-Popers becomes compartmentalized. Thirdly, social disintegration between K-Popers on Twitter appears on fans with different fandoms, that is because they support different idols and consider them as the best of the best. However, if there is an external factor that attacks them, they will reunite and attack it together.